SELULITIS DENGAN ULKUS VARIKOSUM - Mitaart, Andravita F.; Pandaleke, Herry E. J. (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: Cellulitis is an acute bacterial infection of dermis and subcutaneous tissue which manifests as an erythematous lesion with an undefined border accompanied with inflammatory signs. It is mainly found in the elderly; more frequently in females than males; with a history of malaise, fever, and pain as the prodromal signs, and enlargement of local lymph nodes. Cellulitis can occur in any body region, most commonly on the lower limbs, followed by the arms, head, and, neck. It tends to occur in sites with prior lesions such as dermatitis, static ulcers (including varicose ulcers), animal bites, or trauma. A varicose ulcer is an ulcer located on the lower limb caused by a disturbance in the venous blood flow. We reported an 80-year-old woman, presented with cellulitis and varicose ulcers. The diagnosis was based on history, clinical signs, and laboratory findings. The therapy consisted of limb elevation; oral antibiotic clindamycin (300 mg), mefenamic acid (500 mg), and mebhydroline napadisilate (50 mg), each three times daily; and a topical therapy that was comprised of a wound dressing using NaCl 0.9% for 30 minutes three times daily and an application of sodium fusidate cream twice daily. After ten days of therapy, there were clinical improvements with wound healing without any sign of cellulitis.Keywords: cellulitis, varicose ulcerÂ Â Abstrak: Selulitis merupakan infeksi bakteri akut pada dermis dan jaringan subkutan yang ditandai lesi kemerahan berbatas tidak jelas dan disertai tanda-tanda radang. Umumnya selulitis ditemukan pada usia lanjut, perempuan lebih sering daripada laki-laki, dengan riwayat lesu, demam, dan rasa nyeri sebagai gejala prodromal, disertai pembesaran kelenjar getah bening setempat. Selulitis dapat terjadi pada bagian tubuh manapun dengan predileksi pada tungkai bawah diikuti lengan, kepala, dan leher. Selain itu, selulitis biasanya timbul pada lokasi dengan lesi yang telah ada sebelummya, yaitu dermatitis, ulkus stasis (termasuk ulkus varikosum), luka tusuk, gigitan binatang, atau trauma. Ulkus varikosum ialah ulkus pada tungkai bawah yang disebabkan gangguan aliran darah venosa. Kami melaporkan kasus seorang perempuan berusia 80 tahun dengan selulitis dan ulkus varikosum. Diagnosis ditegakkan berdasarkan anamnesis, gejala klinis, dan pemeriksaan penunjang. Penatalaksanaannya ialah elevasi tungkai; antibiotik oral klindamisin 300 mg, asam mefenamat 500 mg, dan mebhidrolin napadisilat 50 mg, masing-masing 3 kali sehari; kompres solusio NaCl 0,9% selama 30 menit 3 kali sehari, dan natrium fusidat krim dioleskan 2 kali sehari. Setelah 10 hari paska terapi, terdapat perbaikan klinis berupa luka yang mulai mengering tanpa disertai tanda-tanda selulitis.Kata kunci: selulitis, ulkus varikosum